A short periconceptional exposure to maternal type-1 diabetes is sufficient to disrupt the feto-placental phenotype in a rabbit model. (15th January 2019) - Rousseau-Ralliard, Delphine; Couturier-Tarrade, Anne; Thieme, René; Brat, Roselyne; Rolland, Audrey; Boileau, Pascal; Aubrière, Marie-Christine; Daniel, Nathalie; Dahirel, Michèle; Derisoud, Emilie; Fournier, Natalie; Schindler, Maria; et al.
Abstract: Tight metabolic control of type-1 diabetes is essential during gestation, but it could be crucial during the periconception period. Feto-placental consequences of maternal type-1 diabetes around the time of conception need to be explored. Using a rabbit model, type-1 diabetes was induced by alloxan 7 days before mating. Glycemia was maintained at 15–20 mmol/L with exogenous insulin injections to prevent ketoacidosis. At 4 days post-conception (dpc), embryos were collected from diabetic (D) or normoglycemic control (C) dams, respectively, and transferred into non-diabetic recipients. At 28dpc, D- and C-feto-placental units were collected for biometry, placental analyses and lipid profiles. D-fetuses were growth-retarded, hyperglycemic and dyslipidemic compared to C-fetuses. The efficiency of D-placentas was associated with an increased gene expression related to nutrient supply and lipid metabolism whereas volume density of fetal vessels decreased. Fetal plasma, placental and fetal liver membranes had specific fatty acid signatures depending on embryonic origin. Tissues from D-fetuses contained more omega-6 polyunsaturated fatty acids. The concentrations of docosahexaenoic acid decreased while linoleic acid increased in the heart of D-fetuses. This study demonstrates that a short exposure to maternal type-1 diabetes in the periconception window, until the blastocyst stage, is able to irreversibly malprogram the feto-placental phenotype, through precocious and persistent structural and molecular adaptations of placenta. Graphical abstract: Highlights: Pre-gestational diabetes in periconception prior implantation, induced persistent embryonic adaptations throughout gestation. Embryo transfer into normoglycemic recipient mothers cannot erase effects of early embryonic programming. Periconceptional diabetes altered placental transporters, leading to fetal hyperglycemia and dyslipidemia but hypotrophy. The periconceptional maternal diabetes induced a fatty acid specific signature in glucose-sensitive feto-placental tissues.